Respuesta :
x²-8x=3
x²-8x+16=3+16=19
(x-4)²=19
x-4=±√19
x=4±√19
x=8.3589 approx or x=-0.3589 approx {4-√19,4+√19} or {-0.3589,8.3589}
x²-8x+16=3+16=19
(x-4)²=19
x-4=±√19
x=4±√19
x=8.3589 approx or x=-0.3589 approx {4-√19,4+√19} or {-0.3589,8.3589}
we know that
[tex](x-a)^{2}=x^{2}-2ax+a^{2}[/tex]
in this problem we have
[tex]x^{2} - 8x = 3[/tex]
so
equate
[tex]-8x=-2ax\\2a=8\\a=4[/tex]
substitute
[tex](x-4)^{2}=x^{2}-8x+16[/tex]
therefore
[tex]x^{2} - 8x = 3[/tex]
[tex]x^{2} - 8x+16 = 3+16[/tex]
[tex]x^{2} - 8x+16 = 19[/tex]
rewrite as perfect square
[tex](x-4)^{2} = 19[/tex]
[tex](x-4) =(+/-)\sqrt{19}\\x=(+/-) \sqrt{19}+4[/tex]
therefore
the answer is
the solution set is
[tex]x1= 4+\sqrt{19}\\x2=4- \sqrt{19}[/tex]